Zamieszkanie w aglomeracji wałbrzyskiej a opłata za gospodarowanie odpadami komunalnymi - Jurek, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Since 1 July 2013 gminas will take over the responsibility for collecting the so-called municipal waste. Owners of occupied and unoccupied properties located within a particular gmina are required to declare the amount of waste management fee. Residence is not always registered and in practice it can be problematic as regards charging the so-called “waste fee” to some owners of unoccupied properties. The determination of the amount of fee favours entities that selectively collect waste. In the case of the Wałbrzych agglomeration, which was established in 2012, the method of calculating waste management fee payable by property owners basically takes into account the number of inhabitants of a property. The fee is the ratio of the number of inhabitants and the rate adopted by the municipal council. The system of municipal waste management is not precise when it comes to the owners of unoccupied or partially occupied properties. The right functioning of the entire municipal waste management system will strengthen public confidence in local government and reflect the environmental awareness of the inhabitants.
Keywords: aglomeracja wałbrzyska; mieszkańcy; właściciele nieruchomości; opłata komunalna; gospodarka odpadami